(untitled) (Scientific journal of the Fergana State University, 2024)
Methods of restoring the physical and psychological condition of children with scoliosis, a disease manifested by the curvature of the spine to one side, have been developed on the basis of hippotherapy exercises. It was found that the set of physical exercises performed on a horse has a positive effect on the functional condition of children with musculoskeletal disorders.